Polypharmacy or potentially inappropriate medications among older adults with COVID-19 in a secondary hospital in China and their association with mortality - Mian Mao; Shan Du; Yue Xu; Qiu Li; Ruoxi Luo; Qiaoqiao Zhou; Xiaoli Hu (Scientific Reports)
Abstract Elderly patients with multiple concomitant chronic diseases are the particularly vulnerable during the Coronavirus disease 2019 (COVID-19) epidemic, which accounts for a large number of COVID-19-related deaths. The purpose of the study was to investigate the impact of polypharmacy and potentially inappropriate medications (PIMs) on in-hospital mortality in a secondary hospital in China. A cross-sectional, retrospective study was conducted using electronic medical data collected from Shanghai Gonghui Hospital from April 2022 to June 2022. Two types of PIMs were adopted, involving the evaluation of the PIM status of older patients with COVID-19 (age ≥ 60 years) identified by AGS/Beers Criteria (PIM-Beers) and the PIM related to Covid-19 antiviral NMV/r (Nirmatrelvir/ritonavir) (PIM-NMV/r). Multivariate logistic regression was used to identify the risk factors associated with PIM use and in-hospital mortality. A total of 617 older COVID-19 inpatients were included in the study. The prevalence of polypharmacy and excessive polypharmacy were 24.6% and 19.1%, respectively. The prevalence of PIMs, PIM-Beers, and PIM-NMV/r were 25.8%, 22.5%, and 60.8%, respectively. Multivariate regression demonstrated that male (OR: 0.57 [95% CI: 0.33–0.98], p = 0.044), diabetes (OR: 2.05 [95% CI: 1.11–3.80], p = 0.023), the more number of medications (OR: 1.44 [95% CI: 1.20–1.72], p < 0.001) and given NMV/r (OR: 3.67 [95% CI: 1.48–9.10], p = 0.005) were influencing factors associated with PIM use. A multivariate logistic regression demonstrated that severe COVID-19 (OR: 6.56 [95% CI: 1.13–38.03], p = 0.036), polypharmacy (OR: 15.43 [95% CI: 3.20-74.29], p = 0.001), excessive polypharmacy (OR: 51.09 [95% CI: 5.23-499.52], p = 0.001), and long-term hospitalization (OR: 0.08 [95% CI: 0.02–0.32], p < 0.001) were influencing factors associated with in-hospital mortality in older COVID-19 inpatients. The polypharmacy and drug-drug interactions of NMV/r were observed in many older COVID-19 inpatients. Older patients with severe COVID-19, a higher number of medications and long-term hospitalization had a higher in-hospital mortality. This result highlights the importance of conducting clinical pharmacists-led medication reviews to identify PIMs of NMV/r and collaboratively working with the physicians to ensure medication appropriateness.